THE INFLUENCE OF LEARNING INDEPENDENCE AND SELF-EFFICACY ON THE WORK READINESS OF CLASS - Tadzkirah Amaliah; Anas Arfandi; Taufiq Taufiq (Universitas Negeri Yogyakarta, 2024)
Background: This research is motivated by the emergence of symptoms of low learning independence which will result in the quality of learning outcomes. This study aims to: 1) Understand the influence of student learning independence on work readiness owned by class XII students of the Construction and Property Business Skills (CPBE) Program at SMK Negeri 2 Makassar, 2) Understand the influence of student self-efficacy on work readiness owned by class XII students of the CPBE Program at SMK Negeri 2 Makassar, 3) Understand the influence of learning independence and student self-efficacy on work readiness owned by class XII students of the CPBE Program at SMK Negeri 2 Makassar.Methods: This research uses a quantitative approach. The population in this study were XII grade students of the CPBE Program at SMK Negeri 2 Makassar, with a sample size of 56 students.Results: Based on the results of the analysis, shows that there is a tendency that the better the learning independence and self-efficacy received, the better the students' work readiness, and vice versa, the lower the learning independence and self-efficacy received by students, the lower the students' work readiness.Conclusion: The conclusions obtained are: 1). There is a positive influence between student learning independence on work readiness of class XII students in the CPBE Program at SMK Negeri 2 Makassar, 2). There is a positive influence between student self-efficacy and work readiness in class XII students of the CPBE Program at SMK Negeri 2 Makassar, 3). There is a positive influence between learning independence and student self-efficacy on work readiness in class XII students of the CPBE Program at SMK Negeri 2 Makassar